2018
DOI: 10.2147/idr.s123887
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant malaria and the impact of mass drug administration

Abstract: Based on the emergence and spread throughout the Greater Mekong Subregion (GMS) of multiple artemisinin-resistant lineages, the prevalence of multidrug resistance leading to high rates of artemisinin-based combination treatment failure in parts of the GMS, and the declining malaria burden in the region, the World Health Organization has recommended complete elimination of falciparum malaria from the GMS. Mass drug administration (MDA) is being piloted as one elimination intervention to be employed as part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…Data show a stalling in declining burden of Plasmodium observed over the last decade (http://apps.who.int/iris/bits tream/10665/259492/1/9789241565523-eng.pdf?ua=1). In addition, the mass drug administration program has shown a limit due to the spreading of multidrug-resistant malaria [2].…”
Section: Introductionmentioning
confidence: 99%
“…Data show a stalling in declining burden of Plasmodium observed over the last decade (http://apps.who.int/iris/bits tream/10665/259492/1/9789241565523-eng.pdf?ua=1). In addition, the mass drug administration program has shown a limit due to the spreading of multidrug-resistant malaria [2].…”
Section: Introductionmentioning
confidence: 99%
“…The representative antimalarial chemotherapy, relying on artemisinin based combination therapy (ACT), primarily targets the infectious strains viz. Plasmodium falciparum and Plasmodium vivax (Lee & Penny, 2019; Newton, Caillet, & Guerin, 2016; Thu, Phyo, Landier, Parker, & Nosten, 2017; Wernsdorfer, 1991; Zuber & Harrison, 2018). However, the depleting susceptibility of the infectious strains to artemisinin, and the eventual resistance to the partner drugs led to a systemic failure of ACTs (Woodrow & White, 2017).…”
Section: Antiplasmodial Activity Of Hybrid Molecules Based On 135‐tmentioning
confidence: 99%
“…Also, previous works have inferred that a potent treatment with ACTs plus primaquine (PQ) would eliminate P. vivax in low transmission settings by implementing programs of mass drug administration [ 41 43 ]. Nevertheless, P. vivax demonstrated an unstable elimination environment, when compared to P. falciparum [ 41 ], since PQ triggers an adverse effect to individuals affected by glucose-6-phosphate-dehydrogenase deficiency (G6PD) questioning mass programs [ 40 , 44 ]. Previous works also indicated that the early development of gametocytes increases P. vivax incidence [ 40 , 45 ].…”
Section: Introductionmentioning
confidence: 99%